PENINGKATAN PENGETAHUAN TENTANG PENCEGAHAN ULKUS KAKI DIABETIK BAGI KADER KESEHATAN - Mulyaningsih, M.; Hermawati (P3M Universitas Aisyiyah Surakarta, 2024)
Background: Diabetes mellitus is a disorder in the body due to hyperglycemia. Diabetes can occur in everyone at any age. Diabetes mellitus is one of the top 10 disease patterns in Surakarta City. The prevalence of DM in Surakarta City is 12,105 cases in 2021. This number is for both insulin-dependent DM patients and non-insulin-dependent DM. Diabetic foot sufferers can experience neuropathic nerve disorders, structural changes, callus skin prints, skin and nail changes, foot injuries, infections, and vascular diseases. The results showed that 50% of DM sufferers had foot defects. As many as 24% were diagnosed with DM with peripheral neuropathy, and 11% had peripheral vascular disease. 60% of all patients are at risk of developing foot ulcers. DM sufferers who experience neuropathy or foot sensitivity can be at risk of developing diabetic foot disease. However, it can be prevented in various ways. For this reason, health cadres need to know what actions must be taken to prevent diabetic foot ulcers. Goals and outputs: to increase the knowledge of health cadres regarding the prevention of diabetic foot ulcers in patients with DM. The activities will be carried out to provide health education about DM and diabetic foot ulcers, teach how to examine feet, and teach foot exercises. Results and Conclusions: There is an increase in knowledge as evidenced by the analysis results, namely the difference between the level of knowledge before and after health education. In addition, there has also been an increase in foot care and exercise skills to prevent diabetic foot ulcers.